Derecho constitucional a la libertad de culto y minorías religiosas - Rodríguez García, Douglas Andrés (2025)
In Ecuador, religious minorities, despite being protected by the Constitution regarding freedom of religion, face various forms of discrimination that make their religious practice difficult. This discrimination includes the lack of access to permits to build places of worship, obstacles in the official recognition of their communities, and harassment by majority sectors, which perpetuates their social marginalization. These barriers reflect a hostile environment that restricts their full participation in public life, underscoring the need for more robust legal and social measures to ensure equal treatment and respect for religious diversity in the country.